Prevalence of Bovine Fasciolosis and Its Economic Loss due to Liver Condemnation at Wolaita Sodo Municipal Abattair, Ethiopia - Zewde, Adane (Vet Med Int, 2019)
Fasciolosis is a serious animal health problem in Ethiopia where cattle raising is very important to the local economy. A cross sectional study was carried out from November 2018 to February 2019 to estimate the prevalence of bovine fasciolosis and its associated risk factors as well as financial losses due to liver condemnation. A total of 247 cattle consisting of 219 males and 28 females were randomly selected and fecal sample collection for Fasciola egg detection and postmortem liver inspection for adult liver flukes, were done. From the total of 247 cattle examined, the overall prevalence of bovine fasciolosis in the study area was 16.6% and 20.24% by coprological and postmortem examinations, respectively. The livers and bile ducts were examined for the adult flukes and the result showed that F. hepatica was frequently detected Fasciola sp. (72%) than F. gigantica (28%). In the study area, the prevalence of bovine fasciolosis between sex was significantly different (p < 0.05) with higher prevalence was recorded in female (57.1%) than male (15.5%). There was also significant association (p < 0.05) among different age groups for the prevalence of bovine fasciolosis with the highest prevalence in older (40.1%) than younger (18.8%) age groups. But, regarding origin and body condition the prevalence of bovine fasciolosis was not significantly associated (p > 0.05). The annual direct financial losses incurred due to fasciolosis were estimated around 1,505, 856 ETB ($43, 024.458). In conclusion, bovine fasciolosis is prevalent and economically important disease in the study area. Therefore, implementation of control and prevention strategy like, grazing managements, reducing the population of the intermediate host, diagnosis and treating sick animals using anthelmintic, is mandatory.